Pedagogies and practice: online teaching during COVID-19 - Afzal Sayed Munna; Md Sadeque Imam Shaikh (Center for Humanities and Innovation Studies, 2020)
At this pandemic situation worldwide, most of the Universities are offering online teaching as an alternative of face-to-face study through Technology-enhanced learning (TEL). To ensure pedagogies and practice for online teaching, we have chosen and critically analyzed the theory “Seven principles for good practice in undergraduate education” by Chickering and Gamson for effective online teaching that researchers highly appreciated. Based on two case studies of two different UK universities and research review, we have also proposed recommendations to implement these seven good practices for online teaching. We have realized that there should be different group discussion forums like café, forums, a conference to engage students to share their ideas, justify their ideas with reliable sources, and finally, reflective thinking and writing, which is essential for learning. Wiki is a good example for group working where everybody shares their ideas about Seven Principles of good practices, then we moderated poster contents and finally prepared the poster the product of knowledge.